'Make in India': a Visionary Campaign of Government of lndia - Mittal , A.K.; Aggarwal, Vimal Kumar (Gyan Management Journal, 2015)
Make in India is an initiative of the Government  of India, to encourage companies to  manufacture their products in India. Prime  Minister Narendra Modi had hinted towards  the launch of Make in India Campaign in his  Independence Day speech of 15 August 2014.  It was launched on 25 September 2014 in a  function at the Vigyan Bhawan. A young nation  with 800 million people under age 35, India is  brimming with optimism and confidence. The  young people's energy, enthusiasm and  enterprise are India's greatest strength.  Unleashing those attributes is the present  government's biggest mission.
Keywords: Government; Prime Minister; Independence Day speech; enthusiasm; enterprise